Analysis of Working Finance at HPCL - Maheshwari, Ajay (Journal of Commerce and Trade, 2017)
An attempt has been made to analyse Working Finance in the context of its size, its adequacy and transmutation i.e., the speed with which it is being turned over from cash to inventories to receivables and to cash again. Profits and generation of cash are also affected by the size of Working Finance. Therefore, profitability has also been studied with reference to Working Finance. Debt-equity ratio affects profitability and the rate of return on investment and therefore the same has also bee analysed. The present study of analysis of working finance in HPCL is unique in the sense that it aims at taking into account the impact of price level changes on the working capital management. The study is based mainly on an analysis and interpretation of published accounts of HPCL. Comparative financial analysis particularly the ratio analysis, funds flow analysis and trend analysis has been made. The study revealed that the planning and programming of materials was not satisfactory. With regard to the items of regular use, the system of automatic replenishment, based on re-order levels, was not followed.